2006
DOI: 10.1002/cne.21071
|View full text |Cite
|
Sign up to set email alerts
|

Synapse loss from chronically elevated glucocorticoids: Relationship to neuropil volume and cell number in hippocampal area CA3

Abstract: Individuals with clinical disorders associated with elevated plasma glucocorticoids, such as major depressive disorder and Cushing's syndrome, are reported to have smaller hippocampal volume. To understand how the hippocampus responds at the cellular and subcellular levels to glucocorticoids and how such changes are related to volume measures, we have undertaken a comprehensive study of glucocorticoid effects on hippocampal CA3 volume and identified elements in the neuropil including astrocytic volume and cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
78
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(80 citation statements)
references
References 59 publications
0
78
0
2
Order By: Relevance
“…If the impact of dentate atrophy on the volume of the hippocampus was proportional, and the dentate contributed 20% of the hippocampal cross-section, a halving of the dentate would be required to produce only a 20% decrease in the parent structure. It is also germane here that glucocorticoid-driven depletion of mitochondria (Coburn-Litvak et al, 2004 ) and synaptic numbers (Tata, Marciano, & Anderson, 2006 ) have been observed in rat hippocampus in the absence of smaller volume.…”
Section: Discussionmentioning
confidence: 61%
“…If the impact of dentate atrophy on the volume of the hippocampus was proportional, and the dentate contributed 20% of the hippocampal cross-section, a halving of the dentate would be required to produce only a 20% decrease in the parent structure. It is also germane here that glucocorticoid-driven depletion of mitochondria (Coburn-Litvak et al, 2004 ) and synaptic numbers (Tata, Marciano, & Anderson, 2006 ) have been observed in rat hippocampus in the absence of smaller volume.…”
Section: Discussionmentioning
confidence: 61%
“…Recent evidence suggests that BDNF and glucocorticoid have converging, homeostatic effects in the nervous system (recently reviewed in references 27, 28, 29, and 30). For example, chronic stress or exogenous glucocorticoid administration suppresses hippocampal BDNF expression, resulting in neuronal atrophy and cognitive impairment (31)(32)(33).…”
mentioning
confidence: 99%
“…Though learning may be primarily related to synaptogenesis and dendritic branching, physical exercise may affect capillaries without increasing neural tissue (Black et al, 1990). In addition, glia may increase in a compensatory manner to balance decreases in synapses (Tata et al, 2006). Thus, experience-dependent volumetric changes cannot always be assumed to originate from changes in the number of synapses per neuron.…”
Section: Microstructural Changes Underlying Changes In Regional Grey mentioning
confidence: 99%